PENGARUH FREE CASH FLOW, EARNINGS POWER, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PRAKTEK MANAJEMEN LABA - Ramadhanty, Dini Rosa; Aprilia, Erika Astriani (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This research aims to determine whether there is an effect of Free Cash Flow, Earnings Power, and Institutional Ownership on Earnings Management. This type of research is quantitative with secondary data in the form of annual financial statements sourced from the Indonesia Stock Exchange (IDX). The population of this study is Non-Cyclical Consumer companies listed on the Indonesia Stock Exchange from 2019 to 2023, thus the selected sample consists of 33 companies using purposive sampling method. The data analysis technique in this study uses multiple linear regression analysis method and the data analysis tool used in this study is Eviews version 12 software. The results show that Free Cash Flow, Earnings Power, and Institutional Ownership together have a significant effect on Earnings Management, Free Cash Flow has a significant negative effect on Earnings Management, Earnings Power has no effect on Management. Institutional ownership does not affect Earnings Management